0403 Efficacy of Once-nightly Sodium Oxybate (ON-SXB; FT218) for Excessive Daytime Sleepiness and Cataplexy: Post-hoc Number Needed to Treat and Effect Size Analyses From REST-ON. (25th May 2022) - Thorpy, Michael; Roth, Thomas; Kushida, Clete; Seiden, David; Dubow, Jordan; Gudeman, Jennifer
Abstract: Introduction: FT218 is an investigational, extended-release, once-nightly formulation of sodium oxybate (ON-SXB) for adults with narcolepsy. ON-SXB treatment achieved significant improvement vs placebo (6 g, 7.5 g, and 9 g, all P<0.001) for the coprimary endpoints of mean sleep latency on the Maintenance of Wakefulness test (MWT), Clinical Global Impression of Improvement rating, and number of weekly cataplexy episodes (NCA), and the secondary endpoint Epworth sleepiness scale (ESS) score, in the phase 3 REST-ON trial (NCT02720744). Post-hoc analyses of numbers needed to treat (NNT) and effect sizes were performed to further contextualize the effectiveness of ON-SXB. Methods: Participants in REST-ON (aged ≥16 years with narcolepsy type 1 or 2) were randomized 1:1 to receive ON-SXB (1 week, 4.5 g; 2 weeks, 6 g; 5 weeks, 7.5 g; 5 weeks, 9 g) or placebo. MWT response was defined as ≥5-min increase from baseline in mean sleep latency, ESS response as a score ≤10, and cataplexy response as ≥50% reduction from baseline in mean NCA. Effect sizes were calculated using Cohen's d; NNTs were the inverse of the absolute risk reduction. Results: The modified intent-to-treat population included 190 participants (ON-SXB, n=97 [NT1, n=73]; placebo, n=93 [NT1, n= 72]). For MWT response, all ON-SXB doses (6 g at week 3, 7.5 g at week 8, and 9 g at week 13) had NNTs of 3 and effect sizes of 0.7–0.9. A dose-response effect was seen for ESS response with NNTs ranging from 3 to 6. Effect sizes were between –0.5 to –0.7 for the 3 doses (decreases signifying response). The NNT for cataplexy response was 6 for ON-SXB 6 g and 3 for ON-SXB 7.5 and 9 g; effect sizes were between –0.7 to –0.8. Conclusion: NNT calculations show that 3–6 patients need to be treated with ON-SXB to achieve ≥5 minutes increased sleep latency on the MWT, ESS score ≤10, or a ≥50% reduction in cataplexy. Considering these post-hoc analyses may be useful to clinicians in discussing treatment expectations and provide support for the efficacy of ON-SXB for excessive daytime sleepiness and cataplexy in adults with narcolepsy.NNT calculations show that 3–6 patients need to be treated with ON-SXB to achieve ≥5 minutes increased sleep latency on the MWT, ESS score ≤10, or a ≥50% reduction in cataplexy. Considering these post-hoc analyses may be useful to clinicians in discussing treatment expectations and provide support for the efficacy of ON-SXB for excessive daytime sleepiness and cataplexy in adults with narcolepsy. Support (If Any): Avadel Pharmaceuticals